Adherence to phase I cardiac rehabilitation in post-PCI patients: a latent class analysis - Zhuo Chai; Yuxuan Fan; Xue Gong; Yue Zhang; Yanling Hu; Xiaowei Li; Zhiqing Fan; Yongkui Han (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary heart disease seriously jeopardizes human health and has become a principal public health problem of global concern. While percutaneous coronary intervention (PCI) repairs narrowed arteries and extends patients' lives, cardiac rehabilitation offers additional benefits post-PCI. Numerous previous studies have shown that cardiac rehabilitation can inhibit the progression of atherosclerotic plaques in patients after coronary intervention, effectively controlling patients' clinical symptoms and improving their quality of life. However, the current status of adherence to phase I cardiac rehabilitation is poor, and the variation in adherence to phase I cardiac rehabilitation among post-PCI patients in China are not well understood. This study aimed to identify the heterogeneity of adherence to phase I cardiac rehabilitation and its influencing factors in post-PCI patients through latent class analysis (LCA) to support individualized interventions.MethodsPCI patients (N = 212) admitted to the Cardiac Rehabilitation Center of Daqing Oilfield General Hospital in Heilongjiang Province were selected to complete the General Demographic Information Questionnaire, Cardiac Rehabilitation Adherence Scale for Coronary Heart Disease Patients, Cardiac Rehabilitation Knowledge Questionnaire, Patient Health Questionnaire-9 (PHQ-9), Social Support Rating Scale, Tampa Scale for Kinesiophobia-Swedish Version (TSK-SV), and Chronic Disease Resource Survey Questionnaire at the end of phase I cardiac rehabilitation. Latent class analysis identified potential categories of adherence to phase I cardiac rehabilitation in post-PCI patients. Logistic regression analyzed the factors influencing the different categories.ResultsAdherence to phase I cardiac rehabilitation in post-PCI patients was classified into three groups: Good Adherence (31.2%), Poor Nutritional and Psychological Management (32.0%), and Lack of Exercise (36.8%). Limited social support, poor utilization of chronic disease resources, low education level, a history of alcohol consumption, and kinesiophobia are factors influencing the different latent subgroups (P < 0.05).ConclusionHeterogeneity exists in the adherence to phase I cardiac rehabilitation of post-PCI patients. Healthcare professionals should implement targeted interventions based on the characteristics of each category to improve adherence.